ANALISA FAKTOR YANG BERHUBUNGAN DENGAN TINGKAT KECEMASAN PADA LANSIA DI PANTI WERDHA HARGODEDALI SURABAYA - Hanaz Rona AQN; Dwi Ernawati; Sapto Dwi Anggoro (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT MOJOKERTO), 2021)
The elderly often experience psychological problems that arise as a result of the aging process, one of which is feeling anxious. Anxiety is an emotional condition in a person that causes feelings of discomfort. This study aims to analyze the factors that influence the incidence of anxiety in the elderly. The design of this research was observational analytic study used cross-sectional approach. The research sample was taken using the Simple Random Sampling technique obtained as many as 36 elderly in Panti Werdha Hargodedali Surabaya. The independent variables in this study were age, education, and length of stay at the orphanage, history of disease, and family support. The dependent variable is anxiety. The instrument used demographic data questionnaire and Gerriatric Anxiety Scale (GAS) questionnaire. Data were analyzed using the Regression Logistic Ordinal test with a significance level of p <0.05. The results showed that anxiety in the elderly was influenced by age (p = 0.018), education (p = 0.003), history of disease (p = 0.005), family support (0.018), and there was no relationship between length of stay at the home (p = 0.532) regarding incidence of anxiety in Panti Werdha Hargodedali Surabaya. The most dominant factor was age factor with regression coefficient value of 1.909. It is expected that the elderly and caregivers could anticipate factors causing anxiety in the elderly and can overcome anxiety problems.